Implementation of the Family Planning Program at a Public Health Centre in a Rural Area - Annisa, Frety Salma; Salianto, Salianto; Hasibuan, Rapotan (Transpublika Publisher, 2025)
Short-term contraceptive methods are predominantly used by 79.2% of participants, while long-term methods account for only 1.0%, far below the RPJMN target of 28.39%. This study aims to assess the implementation of the family planning program at Health Center Rantau Panjang Kiri, focusing on contraceptive preferences and influencing factors. This study employed a qualitative method with a descriptive approach. Data were collected through in-depth interviews, observation, and documentation. Informants included the head of the health center, the person in charge of family planning services, family planning counseling, and reporting, as well as family planning participants and non-participant couples of reproductive ages. Analysis involved data reduction, presentation, and conclusion drawing. The results showed that the implementation of the family planning program at the Rantau Panjang Kiri Health Center went well. However, communication remains a challenge, as some residents lack understanding and counseling is not consistently provided across all villages. Resources including human resources, facilities, and funding are considered adequate. Implementers show positive attitudes, and the bureaucratic structure follows standard operating procedures. In conclusion, the family planning program has been implemented effectively. In terms of communication, some community members still lack a clear understanding of the program. Regarding resources, the program benefits from trained personnel, adequate facilities, and sufficient financial support. The disposition of the implementing staff is generally positive, as indicated by the minimal number of public complaints. From the bureaucratic perspective, the program is carried out in line with established Standard Operating procedures and fragmentation.